Dynamic Monitoring of Grain for Green Program at Chaoyang City, Liaoning Province Based on Landsat Images During 1985—2020 - Shuai Yanmin; Huo Ran; Qu Ge; Shao Congying; Tian Yanjun (Shuitu baochi tongbao)
[Objective] The land cover during the grain for green project (GGP) at Chaoyang City, Liaoning Province were analyzed, and the trend of inter annual land class changes were tracked and monitored, and the impact of the project on barren hills, cultivated land, woodlands, and grasslands at Chaoyang City were discussed, in order to provide scientific support for the rational planning and utilization of land resources at Chaoyang City. [Methods] We used the C5.0 algorithm with Landsat images from 1985 to 2020 to extract the spatial-temporal distribution information of land cover in the region. The dynamic changes and driving factors of forest and grassland in a mountainous area during the 36-year study period were determined by means of land use dynamic attitude and a land use transfer matrix. [Results] ① During the past 36 years, the afforestation area of barren hills at Chaoyang City reached 2 745.5 km2, and the afforestation area of cultivated land was about 933 km2. GGP had achieved remarkable benifits. ② The returned farmland and reforestation areas were mainly located in areas with slopes >25° and altitudes over 500 m. The changes were mainly reflected in the transformation of the internal structure, that is, increasing the proportion of arable land with elevations below 500 m and slopes <25°, basically meeting the requirements of the GGP policy. [Conclusion] The barren hills, cultivated land, forests and grassland of Chaoyang City in the five GGP stages were transformed from one year to another. Compared with the first three GGP stages, the “reverse process” phenomenon in the latter two GGP stages was reduced in response to policy adjustments and implementation. In terms of project implementation, it will still be necessary to strengthen supervision, accurately understand national policies and project technical regulations, and implement policies according to local conditions.